ATTACK RATE OF RICE STEM BORER TO THE VIRIOUS VARIETAS OF RICE (Oryza satuva) - Sahbandi, Sahbandi; RAMADHAN, TRIS HARIS; SARBINO, SARBINO (Jurnal Sains Mahasiswa Pertanian, 2018)
ATTACK RATE OF RICE STEM BORER TO THE VIRIOUS VARIETAS OF RICE (Oryza satuva)Sahbandi1, Tris Haris Ramadhan2, Sarbino3 1Agriculture; Faculty University of Tanjungpura2Agriculture; Faculty University of Tanjungpura3Agriculture; Faculty University of Tanjungpurae-mail: *sahbandi@student.untan.ac.id ABSRTACTRice is an agricultural product in Indonesia that has the largest number of consumers in the world, pests are an important factor in influencing efforts to increase rice production. Rice stem borer is one of the important pests that attack rice plants throughout the country and can reduce the yield of rice, one of the ways in controlling rice stem borer is by planting resistant or tolerant varieties, using resistant or tolerant varieties is an integrated pest management concept (IPM). The purpose of this study is to measure the extent of rice stem borer attack on several rice varieties in the field. The study was conducted in Sub District Rasau Jaya 2, District Kubu Raya, for 4 months from April to July 2017. The research method using Randomized Block Design consisted of 4 varieties with 5 replications ie Inpara 3 (V1), Inpari 30 (V2), IPB 3S (V3) and IPB 4S (V4) data analysis using ANOVA followed by Duncan Mutiple Range Test (DMRT) at 5% level. The results showed that all rice varieties tested were attacked by rice stem borer, with the intensity of the deadhearts and the whitehead different outbreaks, the inpara 3 varieties were categorized as resistant because they had the lowest intensity of deadheart and whithead attacks, the inpari 30 varieties were categorized as susceptible because of the intensity of deadheart and whitehead the highest was higher than in other varieties, the varieties IPB 3S and IPB 4S were categorized rather resistant because at the level of attack that was not significantly different with susceptible varieties but did not decrease the yield significantly.Key words: Deadhearts, intensity, IPM, Rice stem borer, Rice varietas, and whiteheads